Analisis Tingkat Kesehatan Bank Nagari Syariah Menggunakan Metode RGEC - Pratama, Shinta; Shabri, Husni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The purpose of this study was to measure the health level of Bank Nagari Syariah using the RGEC method. The research method used is descriptive quantitative method. The data collection technique used is documentation. The data analysis technique uses ratio analysis contained in the assessment of the bank's health level using the RGEC method. The results showed that the health level of Bank Nagari Syariah in 2017-2022 was in a good rating. In 2017-2018, the Financing to Debt Ratio was in an unhealthy state. But in 2019-2022 the bank has been able to improve its performance. The Net Performing Financing ratio is in a healthy state from year to year. The profitability factor shows that the bank is able to make a profit from its operational activities. Operating Expenses to Operating Income are categorized as healthy. The Good Corporate Governance factor shows that the implementation of the bank's operational structures and processes is in accordance with the regulations set by the OJK. The Capital factor is calculated by the Capital Adequacy Ratio and is in a very healthy state. The health level of Bank Nagari Syariah is in a healthy position.┬á